UNDERSTANDING TABOOS: A WINDOW INTO CULTURE AND SOCIETY - Nigora Yusupova; Melihol Xushboqova; Surayyo Xursandova (TADQIQOTLAR, 2025)
This article explores the concept of taboos across cultures, examining their origins, types, and societal roles. It highlights how taboos function as a reflection of cultural values and norms, while also noting how modern perspectives are reshaping some traditional beliefs. By investigating various examples and considering current shifts, we aim to offer a deeper understanding of how taboos impact individual behavior and collective society.